1998
DOI: 10.1007/s001250050873
|View full text |Cite
|
Sign up to set email alerts
|

Decreased nitric oxide synthase activity in platelets from IDDM and NIDDM patients

Abstract: Nitric oxide (NO) has been shown to inhibit platelet activation through an increase in cytoplasmic cGMP levels [1,2]. Recent evidence suggests that the cGMP increase induced by insulin in human platelets, which accounts for the antiaggregatory effect of the hormone, is mediated by NO [3]. NO production within the platelet is made possible by the presence of a constitutive isoform of the enzyme nitric oxide synthase (NOS) , which has been recently isolated from human platelets [4]. Platelet NOS has a distinct m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
36
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 18 publications
8
36
0
2
Order By: Relevance
“…In agreement with previous studies [11,12], we found that basal NOS activity in platelets from Type 2 diabetic patients was lower than in control subjects. The stimulation of βAR and increased cyclic AMP did not change NOS activity in comparison with basal in platelets from Type 2 diabetic patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous studies [11,12], we found that basal NOS activity in platelets from Type 2 diabetic patients was lower than in control subjects. The stimulation of βAR and increased cyclic AMP did not change NOS activity in comparison with basal in platelets from Type 2 diabetic patients.…”
Section: Discussionsupporting
confidence: 93%
“…A significant inverse correlation between HbA 1c values and basal platelet NOS activity has been found in Type 1 and Type 2 diabetic patients [12]. However, a similar study [11] failed to find any such correlation, while another study [10] reported no correlation between basal cyclic GMP and glycaemic control in people with Type 1 diabetes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A previous work by our group described a decreased NO production in platelets from Type I and Type II diabetic patients, possibly related to the higher sensitivity of these cells to aggregating stimuli [16]. Moreover, a further mechanism causing platelet dysfunction in diabetes related to NO synthesis might be an imbalance between NO and superoxide production, leading to the formation of the powerful oxidant peroxynitrite.…”
Section: Discussionmentioning
confidence: 85%
“…T he endothelial dysfunction observed in the insulin-resistant states of obesity and type 2 diabetes has been attributed to decreased nitric oxide (NO) availability (1,2), likely related to both impaired production and increased consumption (3,4). However, paracrine control of vascular tone depends on the balance of both vasodilating and vasoconstricting factors (5).…”
mentioning
confidence: 99%